Participação de Canais Potencial Receptor Transiente (TRP) no mecanismo de ação vasorrelaxante de rotundifolona em artéria mesentérica de rato - Almeida, Mônica Moura de (2011)
Introduction: The Transient Receptor Potential (TRP) superfamily of cation channels is remarkable since it displays greater diversity in activation mechanisms, and are targets for plant-derived compounds. Aim: To investigate the role of TRP channels in the vasorelaxant response of rotundifolone in the superior mesenteric artery from Lyon Normotensive (LN) rats. Methods and Results: Endothelium-denuded artery rings were suspended by platinum hooks for isometric tension recordings. In nominally free-Ca2+ medium, the rings were submitted to successive phenylephrine (Phe) contractions to deplete Ca2+- stores and contracted to CaCl2 (10-2 M). The maximum response (MR) of CaCl2-contractions in presence of nifedipine (10-6 M) (MR = 31.66 ± 2.27 %) were significantly attenuated in the presence of nifedipine plus rotundifolone (3 x 10-4 and 3 x 10-3 M) (MR = 9.30 ± 2.38 and 1.12 ± 0.31 %) or nifedipine plus menthol (10-4 and 10-3 M) (MR = 10.96 ± 1.34 and 1.52 ± 0.82 %). Rotundifolone caused relaxation of vessels pre-contracted with Phe (MR = 100.32 ± 3.88 %; pD2 = 3.59 ± 0.04, n = 6). The vasorelaxant effect induced by rotundifolone was significantly atenuated in the presence of Gd3+ (10-4 M) (MR = 83.74 ± 5.71 %; pD2 = 3.15 ± 0.06); Gd3+ (2.25 x 10-5 or 2 x 10- 6 M) (pD2 = 3.18 ± 0.06 and 3.32 ± 0.03 %) or BCTC (MR = 76.30 ± 2.15 %; pD2 = 3.46 ± 0.04), but no in the presence of ruthenium red, La3+ or Mg2+, nor after TRPV1 desensitization with capsaicin. Menthol caused relaxation of vessels pre-contracted with Phe (MR = 105.07 ± 3.07 %; pD2 = 3.72 ± 0.02). The vasorelaxant effect induced by menthol was significantly potentiated in the presence of ruthenium red (10-5 M), a non-selective TRP channels blocker (pD2 = 4.12 ± 0,04, n = 6). Also, the vasorelaxant response of menthol was significantly attenuated in the presence of La3+ (8 x 10-5 M), non-selective TRP channels blocker (MR = 89.05 ± 1.61 %); Mg2+ (2.25 x 10-3 M), TRPM3, 6 and 7 selective blocker (MR = 90.76 ± 2.94 %); Gd3+ (10-4 M), TRPV4, TRPC1, 3 and 6, TRPM3 and 4 channels blocker (MR = 73.82 ± 5.44 %); Gd3+ (2.25 x 10-5 M), TRPC3 and 6, TRPV4 channels blocker (MR = 88.04 ± 2.33 %); Gd3+ (2 x 10- 6 M), TRPC6 selective blocker (MR = 89,30 ± 3,61 %) or BCTC (2 x 10-6 M), TRPM8 and TRPV1 channels blocker (MR = 66.77 ± 6.05 %), and after TRPV1 desensitization with capsaicin (10-5 M) (RM = 88.96 ± 4.50). The basal tension was reduced by change in the thermostat temperature from 37 ºC to 25ºC and 18ºC (MR = 21.15 ± 0.78 and 28.84 ± 1.03 %). This response was significantly potentiated by rotundifolone (3 x 10-3 M) (MR = 28.01 ± 1.81 and 38.45 ± 1.98 %) or menthol (10-3 M) (MR = 29.87 ± 1.25 and 43.03 ± 2.22 %). In the way similar to menthol, the effects induced by rotundifolone were attenuated in free-Ca2+ medium plus EGTA (MR = 20.42 ± 1.97 and 30.90 ± 2.58 %) or in the presence of BCTC (MR = 17.05 ± 1.94 and 26.48 ± 3.39 %), but not when the vessels were pre-treated with ruthenium red or capsaicin. The RNAm and the protein of the TRPM8 channel are expressed in the superior mesenteric artery from LN rats. Conclusions: These data suggest that rotundifolone induces concentration-dependent relaxation in the mesenteric artery due to inhibition of ROC and SOC channels (probably TRPC1 and TRPC6) and activation of TRPM8 channels.